Faktor determinan kematian ibu di Kabupaten Sintang periode Agustus 2021 – 2022 - Dian Ika Pratiwi; Heru Subaris Kasjono; Gunarmi Gunarmi; R.Soerjo Hadijono; Yunida Haryanti; Lea Masan (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: indicators of maternal health in a country can be seen through the high and low Maternal Mortality Rate (MMR). Sintang District in 2021 will be the second highest contributor to MMR in West Kalimantan Province. The determinants of maternal mortality are inconclusive and show different results in each region according to the method of collecting maternal mortality data.Objectives: the general objective of this research is to find out the Determinant Factors for Maternal Mortality in Sintang District for the period August 2021 – August 2022.Methods: using a mix of quantitative and qualitative methods with sequential explanatory. Quantitative research samples totaled 16 cases and qualitative informants amounted to 40 informants with indepth interview method. .Results: quantitative proxy determinant of maternal death caused by complications of childbirth (37.5%) 6 cases, determinant intermediate age > 35 years (68.75%) 11 cases and ANC examination (68.75%) 11 cases, contextual determinant geographical area (75%) 12 cases. The qualitative results of the proxy determinants of maternal death were cases of retained placenta bleeding, the determinant intermediate the risk factors for maternal age > 35 years, high maternal parity ≥ 3 times giving birth and incomplete ANC examinations < 6 times. The determinant is far because it is in a rural area.Conclusion: the causes of maternal death in Sintang district are very complex and multifactor. Assistance for high-risk pregnant women by health personnel and monitoring periodic evaluations of the Program Birth Planning and Complication Prevention (P4K) must be carried out to reduce MMR in Sintang District.